2007
DOI: 10.1111/j.1095-8312.2007.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of parsimony analysis of endemicity to Mexican gymnosperm distributions: grid-cells, biogeographical provinces and track analysis

Abstract: Parsimony analysis of endemicity (PAE) was used to analyse the distributional patterns of 124 species of Mexican gymnosperms, using two different sample units: grid‐cells and biogeographical provinces. PAE analyses were based on distributional data from herbarium specimens and specialized literature. Two data matrices were constructed for 60 grid‐cells of 2° and 14 biogeographical provinces. The analysis of the 2° grid‐cell matrix led to 7084 cladograms. The strict consensus cladogram showed several clades equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
15
0
6
Order By: Relevance
“…Grid-cells are a decisive component in biogeographic analyses (Morrone and Escalante 2002;Contreras-Medina et al 2007); therefore, the PAE analysis of the entire Atlantic Forest domain was divided into grid-cells of two different sizes, 1 × 1°a nd 3 × 3°. Applying grid-cells of different sizes to a single data set makes it possible to obtain results that are more complete because different quadrant sizes can be sensitive to different distributional patterns within the same geographic region (the use of small grid-cells can produce poorly resolved area cladograms) (Morrone and Escalante 2002;Contreras-Medina et al 2007). In addition, a study area may contain different levels of endemism in different regions (DaSilva 2008).…”
Section: Parsimony Analysis Of Endemicitymentioning
confidence: 99%
“…Grid-cells are a decisive component in biogeographic analyses (Morrone and Escalante 2002;Contreras-Medina et al 2007); therefore, the PAE analysis of the entire Atlantic Forest domain was divided into grid-cells of two different sizes, 1 × 1°a nd 3 × 3°. Applying grid-cells of different sizes to a single data set makes it possible to obtain results that are more complete because different quadrant sizes can be sensitive to different distributional patterns within the same geographic region (the use of small grid-cells can produce poorly resolved area cladograms) (Morrone and Escalante 2002;Contreras-Medina et al 2007). In addition, a study area may contain different levels of endemism in different regions (DaSilva 2008).…”
Section: Parsimony Analysis Of Endemicitymentioning
confidence: 99%
“…2B): three in the Transmexican Volcanic Belt, one in the southern Sierra Madre Oriental, one in the eastern Sierra Madre del Sur, one in the highlands of Chiapas, and three in the boundaries between two provinces. They concluded that taxa isolated in the highlands of Chiapas (as well as Guatemala) at the end of the Pleistocene may represent the southernmost Nearctic relicts in Mesoamerica, and that the other biogeographic provinces, together with the Sierra Several other studies have contributed to the recognition of similar generalized tracks and nodes, and to the identification of smaller generalized tracks (Luna-Vega et al 1999, 2000, 2001, Morrone et al 1999, Morrone and Escalante 2002, Escalante et al 2003, Márquez and Morrone 2003, Ochoa et al 2003, Morrone and Gutiérrez 2005, Espinosa et al 2006, Contreras-Medina et al 2007a, Mariño-Pérez et al 2007, Toledo et al 2007, García-Marmolejo et al 2008). …”
Section: Identification Of Biotic Componentsmentioning
confidence: 99%
“…Based on species occurrence, biogeographic affinities and provinciality were determined by Parsimony Analysis of Endemism (PAE). This analysis is the most widely used parsimonybased tree algorithm, which from presence/absence distribution data reproduce historical relationships between areas based on species distribution and segregate areas where endemism most possibly evolves (Aguilar-Medrano, Reyes-Bonilla, & Polly, 2015;Casagranda, Taher, & Szumik, 2012;Contreras-Medina, Luna-Vega, & Morrone, 2007).…”
Section: Biogeographic Affinitiesmentioning
confidence: 99%